The Effect of Providing Cognitive Support (Information) on Coping Congestive Heart Failure Patients - Anurogo, Dito; Said, Asbath; Harmanto, Harmanto; Sari, Rina Inda; Solehudin, Solehudin; Nursinah, A. (International Journal of Health Sciences, 2023)
Coping is the way it is done individual in finish problem, adjust self with change, response to threatening situation. Behavior coping formed through change method thinking (cognitive), change behavior or purposeful environment for resolve the stress faced. Behavior coping is also formed through the process of learning, remembering and relaxing. Learn here is ability adapt self (adaptation) to influences internal and external factors. Cognitive is acquisition, arrangement and use encompassing knowledge every related mental behavior with understanding, consideration, processing information, solving problems, gaps and beliefs. Cognitive support (Information) is information or announcement or news. Function information that is as material standard for take decisions, where everyone is in every moment will take right decision need information that is relevant, useful, appropriate, and correct. Change formation cognitive generally started with changes in wishes and information. That information newly acquired somebody can happen change in his thinking. This something beginning for understand deed cognitive.